Bilateral congenatal renal arteriovenous malformation: a rare entity with uncommon presentation - Hassan, Radhiana; Abdullah, Mohd Shafie; MA , Mohd Ariff (Faculty of Medicine, International Islamic University Malaysia, 2009)
Renal arteriovenous malformation (AVM) is a rare congenital anomaly of the urinary system. We present a patient with bilateral renal AVMs who presented with back pain and microscopic hematuria. This case highlights the importance of careful diagnostic work-up in the evaluation of upper tract hematuria.